2020
DOI: 10.13057/biodiv/d220143
|View full text |Cite
|
Sign up to set email alerts
|

Shewanella baltica strain JD0705 isolated from the mangrove wetland soils in Thailand and characterization of its ligninolytic performance

Abstract: Abstract. Chantarasiri A. 2021. Shewanella baltica strain JD0705 isolated from the mangrove wetland soils in Thailand and characterization of its ligninolytic performance. Biodiversitas 22: 354-361. Lignin is a complex biopolymer and the third component by mass of lignocellulosic plant biomass. Its recalcitrant property hampers the hydrolysis and utilization of cellulose and hemicellulose in the lignocellulosic biomass. Thus, the delignification of lignocellulosic biomass is an enormous challenge for emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…It is mostly overgrown by halophilic plants, including Avicennia alba Blume., Bruguiera gymnorrhiza (L.) Lamk., and Rhizophora apiculata Blume (Chantarasiri 2021a). This area was demonstrated as the identical area in the previous studies of Chantarasiri (2015;2021a;2021b) which reported the isolation, genetic identification, and enzymatic characterization of many cellulolytic, phenanthrenedegrading, and ligninolytic bacteria, respectively. Therefore, this mangrove forest was considered as a biodiversity hotspot for a bacterial isolation study in the east region of Thailand.…”
Section: Study Areasupporting
confidence: 59%
See 1 more Smart Citation
“…It is mostly overgrown by halophilic plants, including Avicennia alba Blume., Bruguiera gymnorrhiza (L.) Lamk., and Rhizophora apiculata Blume (Chantarasiri 2021a). This area was demonstrated as the identical area in the previous studies of Chantarasiri (2015;2021a;2021b) which reported the isolation, genetic identification, and enzymatic characterization of many cellulolytic, phenanthrenedegrading, and ligninolytic bacteria, respectively. Therefore, this mangrove forest was considered as a biodiversity hotspot for a bacterial isolation study in the east region of Thailand.…”
Section: Study Areasupporting
confidence: 59%
“…Thirty mangrove soil samples were collected from the Phra Chedi Klang Nam Mangrove Forest. The texture collected soil samples was sandy and muddy clays according to the previous study of Chantarasiri (2021b). The temperature measured in situ by a needle probe thermometer ranged from 28.9°C to 32.0°C, and the average temperature was 30.01  1.61°C.…”
Section: Description Of the Collected Mangrove Soil Samplesmentioning
confidence: 99%